Loyalty As Affecting Mediator Of Service Quality And Customer Satisfaction Towards Competitive Advantage - Mohammad Hamim Sultoni; Sudarmiatin (Institute of Computer Science (IOCS), 2021)
When preparing an effective marketing strategy, a bank must consider its competitors as well as its customers. Establishing a mutual relationship with customers requires a better means of satisfying customer needs than the competitors. Micro, Small, and Medium-sized Enterprises (MSMEs) should always analyze their competitors and develop marketing strategies that effectively give the company a good position compared to the competitors and provide a competitive advantage as strong as possible. This research was conducted using a quantitative method. The design was categorized as causal relationship research. The data were then analyzed using the path analysis. Findings of the research showed that customer satisfaction, service quality, and customer loyalty affected the competitive advantage of Sentra Batik Pamekasan. The effect of customer loyalty on the competitive advantage could be observed from the number of Sentra Batik Pamekasan’s customers who decided not to move to other financial institutions (banks). When the company could give better service quality, the customer loyalty and the competitive advantage among financial institutions would get higher.